2017
DOI: 10.1017/s0954579417001237
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of pre- and postnatal maternal stress on infant temperament and autonomic nervous system reactivity and regulation in a diverse, low-income population

Abstract: We examined the prospective associations of objective and subjective measures of stress during pregnancy with infant stress reactivity and regulation, an early-life predictor of psychopathology. In a racially and ethnically diverse low-income sample of 151 mother-infant dyads, maternal reports of stressful life events (SLE) and perceived stress (PS) were collected serially over gestation and the early postpartum period. Infant reactivity and regulation at 6-months of age was assessed via maternal report of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 122 publications
4
112
3
Order By: Relevance
“…Third, many associations were examined, thus increasing the likelihood of chance associations. However, since previous associations between family death, anxiety, depression, and oxidative stress have been observed in non‐pregnant populations, it is unlikely that these results occurred by chance. In addition, TIDES has not yet extracted detailed information on birth outcomes, therefore gestational age was not examined as part of these analyses despite associations between oxidative stress and gestational age in previous studies .…”
Section: Commentmentioning
confidence: 95%
See 2 more Smart Citations
“…Third, many associations were examined, thus increasing the likelihood of chance associations. However, since previous associations between family death, anxiety, depression, and oxidative stress have been observed in non‐pregnant populations, it is unlikely that these results occurred by chance. In addition, TIDES has not yet extracted detailed information on birth outcomes, therefore gestational age was not examined as part of these analyses despite associations between oxidative stress and gestational age in previous studies .…”
Section: Commentmentioning
confidence: 95%
“…Second, we explored effect measure modification by maternal race/ethnicity, infant sex, and study site. Third, we examined associations between SLEs and 8‐iso‐PGF 2α within strata of “good” and “poor” psychosocial status with the hypothesis that women with higher levels of psychological distress would have greater elevations in oxidative stress in response to external stressors like SLEs …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, at birth, infants who are exposed to high levels of prenatal stress, evidenced by elevated maternal cortisol levels, show a concomitant higher level of cortisol as well, and such elevations persist into early childhood [38]. Bush et al [41] also found that prenatal exposure to high levels of maternal stress affected temperamental characteristics and parasympathetic nervous system responses, both associated with early identification of later psychopathology. Similarly, children exposed to high levels of stress in early childhood may show effects well into adolescence [38].…”
Section: Stress Response Systemmentioning
confidence: 99%
“…A growing literature reveals individual differences in maternal experiences regulate infant behavior and biology (Ostlund, Measelle, Laurent, Conradt, & Ablow, ). Specifically, prenatal stress, anxiety, and mood disturbances (e.g., depression) are associated with child outcomes such as low infant birth weight and preterm birth (Dunkel Schetter, ), aberrations in neurodevelopment (van den Bergh et al, ), behavioral and emotional problems (Bush et al, ; MacKinnon, Kingsbury, Mahedy, Evans, & Colman, ; Nolvi et al, ), and poor cognitive development (Bergman, Sarkar, O'Connor, Modi, & Glover, ; Schechter et al, ). Alterations to the in utero environment can even have long‐term implications for the child's behavior and physiology (Hocher, ; Rakers et al, ).…”
Section: Introductionmentioning
confidence: 99%